2021
DOI: 10.1111/anu.13257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of prophylactic health products on water quality and shrimp ( Penaeus monodon ) performance at the nursery phase

Abstract: The aim was to assess the efficacy of prophylactic health products (PHPs) on shrimp (Penaeus monodon) post larvae (PL) during the nursery phase. This included five treatments: infeed probiotic (F_PRO), water probiotic (W_PRO), a combination of water and infeed probiotic (FW_SYN), biofloc, a combination of biofloc and infeed probiotic (F_PRO&biofloc), and a no‐treatment control, five replicates each. Each tank was filled with 450 L water and stocked with 700 PL15, weight 0.008 ± 0.00 g at a density of 1.56 PL/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These results indicated that the adoption of nursery systems can increase the efficiency of shrimp farming. Notably, high-density nursery systems using microbial approaches have also been successfully employed using P. monodon [91,92], and other penaeid species such as Farfantepenaeus paulensis [93], L. setiferus [94], and F. brasiliensis [95]. One study on L. vannamei BFT nursery systems reported no difference in PL performance when compared to a conventional microalgaebased system [96].…”
Section: Nursery Systemsmentioning
confidence: 99%
“…These results indicated that the adoption of nursery systems can increase the efficiency of shrimp farming. Notably, high-density nursery systems using microbial approaches have also been successfully employed using P. monodon [91,92], and other penaeid species such as Farfantepenaeus paulensis [93], L. setiferus [94], and F. brasiliensis [95]. One study on L. vannamei BFT nursery systems reported no difference in PL performance when compared to a conventional microalgaebased system [96].…”
Section: Nursery Systemsmentioning
confidence: 99%